ANALISIS TENTANG PERAN GURU DALAM MEMBENTUK KARAKTER KREATIF SISWA DI SMA NEGERI 1 KERITANG KELURAHAN KOTABARU RETEH KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Amir Ahmad Ma’ashabri; Hambali Hambali; Sri Erlinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the fact that there are many students who are lacking in developing their creativity both in learning and outside of class hours such as less participation in active learning, lack of participation in various extracurriculer activities and most students tend to be lazy in follow class hours. This is what makes the writer interested in do the research. The formulation of the problem in this research is how the theacher’s role in shaping the creative character of students in SMA Negeri 1 Keritang Kotabaru reteh Keritang Village Indragiri Hilir Regency. This study aims to determine the role of the theachers in shaping the creative character of students in SMA Negeri 1 Keritang. This research was conducted from march-november 2020. The total population of this study amounted to 834. The sampling technique used the random sampling tecnique with a sample size of 90 people using the slovin formula. The data collection techniques used were questionnaires, interviews, observation and documentation. In analyzing the data, researcher used quantitative descriptive methods. The results of this study indicate that the percentage of respondents who answer very well + Good is 96.56% where the Very Good category is the range of 75.01%-100%. It can be concluded that the analysis of the role of theachers in shaping the creative charachter of students in SMA Negeri 1 Keritang Kotabaru Reteh Keritang Village Indragiri Hilir Regency is included in the “Very Role” category.Key Words:Theacher Role,Creative Character